Increasing the effectiveness of the tool development process through partnership - Johansson, Charlotta (Luleå tekniska universitet, Arkitektur och vatten, 2002)
Partnership is about developing good business relations between two or more companies. It is a simple and effective working method that can be applied in many situations, including developing new products and associated tooling which is the focus of this thesis. The goal with partnership is not to have a cosy relationship between the partners; but rather as an effective way to make money using a simple working method. The work presented in this thesis is the result of a joint project between Luleå University of Technology and the Pressoform consortium. Pressoform was interested in applying the results in the tooling industry in Sweden and therefore funded the research. The aim of the work behind this thesis was to show that by implementing an effective working method, based on partnership, product development lead-times could be reduced without reduction in quality or increased costs. The specific domain of the work was the development process for form tools such as tools for injection moulding, die casting and sheet metal forming. The advantages with working in a partnership include the possibility to achieve a reduced lead-time and at the same time increase quality and reduce the cost by using an effective working method for developing new products. There are however risks with partnerships, it is a more expensive relationship to maintain, customers are more tightly bounded to suppliers. Another risk could be that the customers by tradition have looked for a power relationship, where they control the form of the relationship. On the other hand a partnership may result in customers and suppliers becoming too close and loose the business like attitude. Partnership is a long-term investment and a strategy for the companies involved to make more money in the long term. Personal relations and trust are important in a long-term strategy, since the companies expect to work together for a long period of time. Partnership should therefore only be conducted with companies that are trusted. In addition effective methods ...